2015
DOI: 10.1039/c5ra12552a
|View full text |Cite
|
Sign up to set email alerts
|

Pd nanoparticles supported on reduced graphene–E. coli hybrid with enhanced crystallinity in bacterial biomass

Abstract: A novel method for simultaneous reduction of graphene oxide (GO) and palladium salt, Pd (II), using Escherichia coli in the separate presence of two different mild reducing agents (hydrogen and formate) is investigated to successfully produce reduced GO (rGO)-biomass/Pd hybrid material for potential use as an electrocatalyst. Transmission electron microscopy, X-ray diffraction, thermogravimetric analysis, X-ray photoelectron spectroscopy and Raman microscopy demonstrate the successful reduction of Pd (II), GO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Component peaks for the three samples can be seen in the deconvoluted spectra in Figure 9B–D. Components identified in the three spectra were similar to those reported in similar bacterial systems reported earlier (Priestley et al, 2015; Gomez-Bolivar et al, in review). In the case of bimetallic CAS, the extended Ru 3d 5/2 region (in which the Ru components are more easily identifiable compared to Ru 3d 3/2 which is overshadowed by C 1s components), suggested the presence of an additional Ru component near 279.7 eV.…”
Section: Resultssupporting
confidence: 85%
“…Component peaks for the three samples can be seen in the deconvoluted spectra in Figure 9B–D. Components identified in the three spectra were similar to those reported in similar bacterial systems reported earlier (Priestley et al, 2015; Gomez-Bolivar et al, in review). In the case of bimetallic CAS, the extended Ru 3d 5/2 region (in which the Ru components are more easily identifiable compared to Ru 3d 3/2 which is overshadowed by C 1s components), suggested the presence of an additional Ru component near 279.7 eV.…”
Section: Resultssupporting
confidence: 85%
“…45 The cell membrane contains organic compounds, mainly phospholipids, and also proteins and attached polysaccharide chains 46 and oxidative attack on various functional groups of the membrane may be a key mechanism leading to heat-induced cell death 47 and lipids are the most vulnerable. In support of this, studies using XPS (a surface technique, which probes the outer membrane ∼5-10 nm) have shown an effect of Pd on cells of E. coli 27 while some reduction of Pd(II) in the absence of added electron donor was observed using D. desulfuricans (NCIMB 8307 and NCIMB 8326) suggesting a function of Pd(II) as an oxidant (J.B. Omajali and L.E. Macaskie, unpublished).…”
Section: Discussionmentioning
confidence: 90%
“…However, catalytically active materials synthesized using these bacteria have mostly been produced in dry powdered form following drying of the metallized cells. A recent study has shown that, contrary to reports that Pd‐NP (palladium nanoparticle) localization is restricted to the surface layers, cells of Bacillus benzeovorans , Desulfovibrio desulfuricans and Escherichia coli have shown extensive deposition of small intracellular Pd‐NPs which implies a mechanism of cellular ‘trafficking’ of the Pd(II) initially applied. ‘Next generation’ biocatalysis would involve ‘tandems’ whereby both Pd‐NPs and biochemical processes contribute to single cell ‘nanofactories’ as illustrated by Foulkes et al .…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst obtained using both strategies showed low power outputs and while Xiong et al (2015) had a more durable catalyst than 20%Pt/C; it had a poor mass activity relative to current commercial catalysts such as TKK (0.016 vs. 0.2 mA/µg). Following co-synthesis of a material by Priestley et al (2015) which comprised Pd(0), reduced graphene oxide and contributory E. coli bacteria (but was not tested for catalytic activity). Liu et al (2016) developed a similar concept where S. oneidensis-Pd/Au NPs were synthesized using graphene oxide (GO) sheets for the anodic reaction.…”
Section: Electrochemical Characterization and Performance Of The Bio-mentioning
confidence: 99%
“…It is timely to develop further the direct use of bacteria as a NP-support for a possible high electrochemical activity coupled with enhanced durability. In addition, it is important to limit costs in synthesis to remain competitive as a catalyst; the incorporation of additional components such as reduced graphene oxide (rGO) (Liu et al, 2016) to improve conductivity and prevent NP agglomeration, may undermine the advantages delivered by this method; the synergistic co-use of E. coli and rGO was previously shown to make a potentially useful material but this was not tested operationally (Priestley et al, 2015) against chemical comparators. Finally, the bacterial strain used affects the nanoparticle localization within the cell and hence bacterial strain choice is an important consideration.…”
Section: Introductionmentioning
confidence: 99%